2020
DOI: 10.1111/jcmm.15030
|View full text |Cite
|
Sign up to set email alerts
|

miR24‐2 accelerates progression of liver cancer cells by activating Pim1 through tri‐methylation of Histone H3 on the ninth lysine

Abstract: Several microRNAs are associated with carcinogenesis and tumour progression. Herein, our observations suggest both miR24‐2 and Pim1 are up‐regulated in human liver cancers, and miR24‐2 accelerates growth of liver cancer cells in vitro and in vivo. Mechanistically, miR24‐2 increases the expression of N6‐adenosine‐methyltransferase METTL3 and thereafter promotes the expression of miR6079 via RNA methylation modification. Furthermore, miR6079 targets JMJD2A and then increased the tri‐methylation of histone H3 on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…The current data suggest that H3K27ac of histones and hypomethylation at promoters can increase METTL3 expression in gastrointestinal cancer [33,53]. Non-coding RNA ARHGAP5-AS1 [38], miR-24-2 [47], and miR-4429 [36] can also regulate METTL3 expression and influence the progression of gastrointestinal cancers. Whether there are other histone modifications or non-coding RNAs involved in the regulation of METTL3 needs further research and exploration.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The current data suggest that H3K27ac of histones and hypomethylation at promoters can increase METTL3 expression in gastrointestinal cancer [33,53]. Non-coding RNA ARHGAP5-AS1 [38], miR-24-2 [47], and miR-4429 [36] can also regulate METTL3 expression and influence the progression of gastrointestinal cancers. Whether there are other histone modifications or non-coding RNAs involved in the regulation of METTL3 needs further research and exploration.…”
Section: Discussionmentioning
confidence: 63%
“…METTL3 could promote glycolysis via activation of the mTORC1 pathway and accelerate lipogenesis by enhancing LINC00958 RNA transcript stability [48], which contributes to HCC progression. In addition, METTL3 promotes the malignant process of HCC through YTHDF2dependent silencing of SOCS2 [50] and the promotion of miR6079 expression [47]. Furthermore, METTL3 triggers polysome-mediated translation of Snail mRNA to accelerate the EMT process of HCC [49].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al showed in gastric cancer that P300 mediates histone H3 acetylation at lysine 27 (H3K27ac) and promotes METTL3 transcription [ 58 ]. It was also reported that microRNA miR-24-2 might promote METTL3 transcription; however, the detailed mechanism remains elusive [ 59 ]. Several other microRNAs, including miR-186, miR-4429, miR-600, and let-7g [ 60 63 ], were proposed to suppress METTL3 by targeting METTL3 mRNA.…”
Section: Regulation Of Mettl3 Expression and M 6 Amentioning
confidence: 99%
“… Oncogene Acute myeloid leukemia MYC , BCL2 , PTEN Promote translation Differentiation, apoptosis [ 73 ] CEBPZ SP1 , SP2 Promote translation Cell cycle regulation, differentiation [ 74 ] Breast cancer let-7g HBXIP Promote translation (?) Cell proliferation [ 63 ] BCL2 Promote translation Proliferation, apoptosis [ 75 ] Liver cancer SOCS2 RNA decay by YTHDF2 Proliferation, migration [ 76 ] RDM1 Proliferation [ 77 ] LINC00958 RNA stabilization Lipogenesis, proliferation, migration, invasion [ 78 ] SUMO1 Snail RNA stabilization Metastasis [ 79 ] Snail promote translation by YTHDF1 EMT [ 80 ] miR24-2 miR-6097 , Pim1 Tumor growth [ 59 ] CTNNB1 RNA stabilization Tumor growth [ 81 ] miR-186 Wnt/β-catenin Proliferation, migration, invasion [ 60 ] Glioblastoma SOX2 RNA stabilization by ELAVL1 Dedifferentiation [ …”
Section: Mettl3 Functions As An M 6 a Methyltransfmentioning
confidence: 99%
“…It was reported that miRNAs participated in regulation of HCC 26 , 27 . For instance, miR‐369 was downregulated in papillary thyroid cancer and inhibited papillary thyroid cancer cells proliferation by downregulating TSPAN13 15 .…”
Section: Discussionmentioning
confidence: 99%